Impact of Spiritual Intelligence on Perceived Stress among Male and Female University Students - Navya, G.; Sharma, S. (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted in the year 2021 to assess the impact of spiritual intelligence on perceived stress among male and female university students. The sample consisted of 160 youth aged between 23-24 years. Multi stage purposive random sampling was employed to draw sample from five constituent colleges of Punjab Agricultural University, Ludhiana who were equally distributed over the gender (80 males and 80 females). The objectives of the study were to assess and compare the level of spiritual intelligence and perceived stress in male and female university students. Spiritual intelligence questionnaire and stress scale were used as data collection tools to assess the spiritual intelligence and perceived stress of university students. The results revealed that spiritual intelligence was significantly high in female respondents against males and male respondents were found to have significantly greater perceived stress as compared to their female counterparts in all the dimensions namely pressure, physical stress, anxiety and frustration. Regression analysis proved that spiritual intelligence had negatively contributed to perceived stress revealing that with increase in spiritual intelligence, perceived stress was reduced in males and females significantly. The present study will be useful for the youth to understand the importance of spiritual intelligence and how it can impact on perceived stress. It would be also helpful for parents, counsellors, psychologists and human development professionals to understand the level of the stress among youth and thus can provide a better environment.